Trust, Technology, and Zakat: Understanding the Participation of Productive Muzakki Among Young Professionals in Islamic Philanthropy - Maghfirah, Maghfirah; Anto, Irma Romi; Maulidizen, Ahmad; Syahrin, M. Alpi; Setiawan, Alfiandri (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
The sustainability of zakat institutions in contemporary Muslim societies increasingly depends on the active participation of young professionals as productive muzakki. However, declining institutional trust and the rapid expansion of digital philanthropic platforms have reshaped patterns of religious giving. This article examines the interrelationship between trust, technology, and zakat participation among young professionals, focusing on how digitalization influences perceptions of accountability, transparency, and religious legitimacy in Islamic philanthropy. Employing a qualitative library-based approach, this study critically analyzes classical fiqh literature, contemporary Islamic economic thought, and recent interdisciplinary scholarship on digital religion and philanthropic behavior. The analysis reveals that trust functions as a multidimensional construct encompassing institutional credibility, procedural transparency, and perceived alignment with Islamic ethical values. Digital technologies—such as online payment systems, mobile applications, and data-driven reporting—emerge as double-edged tools: while they enhance efficiency and accessibility, they also generate new forms of skepticism related to data integrity, commodification of worship, and shifting religious authority. Among young professionals, zakat participation is increasingly shaped by rational-ethical considerations, including measurable social impact, governance standards, and value congruence, rather than purely normative obligations. This article argues that productive muzakki engagement in the digital age requires a reconceptualization of zakat governance that integrates technological innovation with ethical accountability and maqāṣid-oriented objectives. By proposing a conceptual framework linking trust formation, digital infrastructure, and religious motivation, this study contributes to broader debates on Islamic philanthropy, digital religion, and faith-based social finance. The findings offer theoretical insights for scholars and practical implications for zakat institutions seeking to strengthen legitimacy and long-term engagement among younger, professionally active donors.